David Hume and Copernicanism : Hume's appraisal of copernicanism and galileo's "proofs" of the copernican system - Manzo, Silvia
The aim of this paper is to examine how far Hume knew about astronomy, in order to understand the reasons that founded his acceptance of Copernicanism. My contention is that Hume's positive reception of the Copernican system arises at least from the importance that the conferred to three features that he attributes to the Copernican system: beauty, simplicity and uniformity. I also give some evidence that Hume had first-hand knowledge of some sections of Galileo's Dialogo sopra i due massimi sistemi del mondo tolemaico e copernicano (1632), where the "sole proofs" de the Copernican system are said to be found.